ON COMPLETE MONOTONICITY OF THREE PARAMETER MITTAG-LEFFLER FUNCTION - Górska, Katarzyna; Horzela, Andrzej; Lattanzi, Ambra; Pogány, Tibor K. (Applicable analysis and discrete mathematics, 2021)
Using the Bernstein theorem we prove the complete monotonicity of the three parameter Mittag—Leer function E α , β γ ( − ω ) for w ≥ 0 and suitably constrained parameters α, β and γ.